2022
DOI: 10.1002/ccr3.5562
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐induced parkinsonism responsive to intranasal insulin: A case report

Abstract: Here, we introduced a patient with Mn‐induced parkinsonism who was responsive to intranasal insulin, and his parkinsonism and dystonia responded to this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For a long time, there has been some controversy about Mn-induced dopaminergic alterations; whereas some researchers reported that Mn alters dopaminergic innervation, particularly in the basal ganglia, and produces Parkinson-like disorder [14][15][16][17][18] many authors suggested that Mn neurotoxicity is unlike from PD in symptoms, pathology, and etiology [18,19], particularly in the evident preservation of SNc dopaminergic somas [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, there has been some controversy about Mn-induced dopaminergic alterations; whereas some researchers reported that Mn alters dopaminergic innervation, particularly in the basal ganglia, and produces Parkinson-like disorder [14][15][16][17][18] many authors suggested that Mn neurotoxicity is unlike from PD in symptoms, pathology, and etiology [18,19], particularly in the evident preservation of SNc dopaminergic somas [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%